Incidence of oral lichen planus in perimenopausal women: A cross-sectional study in Western Uttar Pradesh population - Ravi Prakash Sasankoti Mohan; Akanksha Gupta; Nagaraju Kamarthi; Sangeeta Malik; Sumit Goel; Swati Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Hormonal fluctuations during menopause lead to endocrine changes in women, especially in their sex steroid hormone production. Studies have documented the role of estrogen and progesterone (Pg) on autoimmune disorders such as multiple sclerosis, systemic lupus erythematosus, and rheumatoid arthritis. Lichen planus (LP), an autoimmune disorder, seen frequently in perimenopausal women, may also get affected by sex steroid hormones, but no direct relationship has been established yet. Aim: The aim of this study is to find the incidence of oral LP (OLP) in perimenopausal women and evaluate the factors associated with it. Materials and Methods: This cross-sectional study was conducted over a period of 1 year. All the perimenopausal women (44.69 ± 3.79 years) who came to the dental outpatient department were evaluated for the presence of LP and various factors associated with it. Depression Anxiety Stress Scale-21 questionnaire was used for psychometric evaluation of perimenopausal women. Results: According to our study, incidence of LP in postmenopausal women was 10.91%, which is higher than incidence of LP in general population, i.e., 0.5% to 2.0%. Incidence of LP increased with the severity of depression in perimenopausal women (P = 0.000). Conclusion: The incidence of OLP is higher in perimenopausal women than in general population and increases significantly with increase in the severity of depression. LP in perimenopausal women can be mediated by declined level of estrogen and Pg directly or indirectly through causing depression that can trigger LP.